Pesantren Business Entity Development As An Education Basis For The Autonomy Of Santri, Pesantren, And The Community: A Case Study At Pesantren Sidogiri Pasuruan - Anis Humaidi (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2021)
This article discusses the Business Entity condition of Pondok Pesantren Sidogiri, the involvement of santri and communities in Pondok Pesantren Sidogiri's Business Entity, and the contribution of Business Entities towards Pondok Pesantren Sidogiri, santri and their communities. This article was prepared using a qualitative case study type method. This article concludes that Pondok Pesantren Sidogiri have a Business Entity. Business entities owned by Pondok Pesantren Sidogiri has established three Perseroan Terbatas stands for PT (Limited Company). PT. Sidogiri Mitra Utama serves the needs of santri, PT. Sidogiri Mandiri Utama, engaged in bottled drinking water and PT. Sidogiri Pandu Utama, engaged in the Outsourcing Provider and Training Center. The involvement of santri and the community around these two Pondok Pesantren in managing the Business Entity is quite active. This active participation implies that these very diverse Business Entities are all oriented towards improving welfare. So that the existence of Business Entity's Pondok Pesantren positively contributes to the independence of santri, Pondok Pesantren, and the community.